Correlation analysis between single nucleotide polymorphisms in ADSL gene andIMP content in chicken - BAO, W B; SHU, J T; MUSA, H H; ZHANG, X Y; CHEN, G H (The Indian Journal of Animal Sciences, 2011)
This study was designed to investigate the effect of adenylosuccinate lyase (ADSL) gene on inosine monophosphate content (IMP) in chicken. Exogenous Recessive White chicken and indigenous Chinese chicken breeds such as Silkies, Baier, Tibetan and Xiaoshan were used. Thirteen pairs of primers were designed to scan all exons of ADSL gene by PCR-SSCP, mutation detected was directly sequenced. A silent mutation at 3484bp in exon 2 was substitute C/T SNP, whereas point mutation at 9839bp in exon 9, was alter C/A SNP and his corresponding amino acid (Pro→Thr). Individuals with TT genotype in exon 2 had significantly higher IMP content than those with CT and CC genotype; in contrast different genotypes in exon 9 were no significantly affected IMP content. We putatively drew the conclusion that SNP in exon 2 of ADSL gene could be used as the potential molecular marker for meat quality trait in chicken.